Unjustified enrichment : key issues in comparative perspective / edited by David Johnston and Reinhard Zimmermann. - Johnston, David, 1961-; Zimmermann, Reinhard, 1952 October 10- (Cambridge University Press, 2002)
Unjustified enrichment has been one of the most intellectually vital areas of private law. There is, however, still no unanimity among civil-law and common-law legal systems about how to structure this important branch of the law of obligations. Several key issues are considered comparatively in this 2002 book, including grounds for recovery of enrichment, defences, third-party enrichment, as well as proprietary and taxonomic questions. Two contributors deal with each topic, one a representative of a common-law system, the other a representative of a civil-law or mixed system. This approach illuminates not just similarities or differences between systems, but also what different systems can learn from one another. In an area of law whose territory is still partially uncharted and whose borders are contested, such comparative perspectives will be valuable for both academic analysis of the law and its development by the courts.